FACTORS INFLUENCING THE PURCHASE DECISION OF ORGANIC TOFU - Tantry Nugroho; Ujang Sumarwan; Kirbrandoko Kirbrandoko (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
This study aimed to analyze the factors that influence consumers in making the decision to buy organic tofu. The theory of factors that influence the purchasing behavior developed by Kotler was used as the analytical tool, and these factors include cultural factors, social factors, personal factors, psychological factors and purchasing process. These data were collected through interview techniques and analyzed descriptively using multinomial logistic regression. The characteristics of respondents indicated the consumers who never bought organic tofu are mostly at the age of 26-35 years old and university graduates, do not work, have an expenditure from Rp 1 million to Rp 2.5 million, are highly knowledge, and have the highest scores on the perceptions on sustainable and environmentally friendly organic farming, health benefits, and a more expensive price. There are a number of factors that influence consumers in making purchase decisions of organic tofu including age, education, knowledge and product external factors. The consumers who are potentially interested in purchasing the organic tofu are at the age of 36–50 years old, university graduates, highly knowledgeable in food and organic tofu products, because the higher the education and knowledge, the greater the interest in buying the products, and they approved of the external products such as price, advertising, personal selling and places of selling which are also potentially equal. The managerial implications for the business agents of tofu organic product is that they must be more active in assuring the consumers that these products are good for them by creating a blog, an ad in the local paper, or a pamphlet containing information of the product.Keywords: purchase decision, logistic regression, organic tofu product, purchasing interestAbstrakPenelitian ini bertujuan menganalisis faktor yang mempengaruhi konsumen dalam melakukan pengambilan keputusan membeli tahu organik. Sebagai alat analisis digunakan teori faktor-faktor yang mempengaruhi perilaku pembelian yaitu teori yang dikembangkan oleh Kotler dimana faktor-faktor tersebut adalah: faktor budaya, faktor sosial, faktor pribadi, faktor psikologis dan proses pembelian. Data ini dikumpulkan melalui teknik wawancara serta dianalisis secara deskriptif dan uji regresi logistik multinomial. Karakteristik responden menunjukkan konsumen yang sudah pernah membeli sebagian besar berada pada usia 26–35 tahun, berpendidikan perguruan tinggi, tidak bekerja, berpengeluaran 1–2,5 juta, memiliki pengetahuan tinggi, memiliki persepsi setuju dengan skor tertinggi mengenai pertanian organik berkelanjutan, ramah lingkungan, manfaat kesehatan dan harga yang lebih mahal. Terdapat faktor-faktor yang mempengaruhi konsumen dalam pengambilan keputusan pembelian tahu organik diantaranya usia, pendidikan, pengetahuan dan faktor eksternal produk. Konsumen yang berpotensial dan berminat membeli tahu organik terdapat pada usia 36–50 tahun, pendidikan tamatan perguruan tinggi, pengetahuan yang tinggi mengenai pangan serta produk tahu organik, karena semakin tinggi pendidikan dan pengetahuan maka akan semakin besar minat membeli, serta konsumen yang setuju mengenai eksternal produk seperti harga, iklan, personal selling dan tempat penjualan juga berpotensi sama. Implikasi manajerial bagi pelaku bisnis produk tahu organik adalah lebih giat dalam meyakinkan produk tersebut terbukti baik bagi konsumen, seperti membuat blog atau membuat iklan di koran lokal, atau pamflet yang berisikan info dari produk.Kata kunci: keputusan pembelian, regresi logistik, produk tahu organik, minat membeli